KONSERVASI NILAI-NILAI PANCASILA DALAM FALSAFAH HIDUP “SEPINTU SEDULANG” MASYARAKAT MELAYU BANGKA - Irawan, Hendri; Wijayanti, Tutik; Adrian , Krisna; Anggraeni, Leni (Indonesian Journal of Conservation, 2024)
Pancasila as a philosophical system derived from the values inherent in the Indonesian nation serves as the state philosophy and a way of life. The internalization of Pancasila values is crucial to ensure that the younger generation develops a strong sense of national identity as Indonesians. This article analyzes: (1) the Pancasila values within the philosophy of life of the Bangka Malay community, known as “sepintu sedulang”, and (2) the internalization of Pancasila values in the“sepintu sedulang” philosophy through civic education learning. The methodology employed in this article is literature study. The findings indicate that the “sepintu sedulang” philosophy of the Bangka Malay community, manifested in the Nganggung tradition, encompasses Pancasila values such as religiosity, humanism, mutual cooperation, solidarity, and justice. Furthermore, civic education serves as a vital medium for internalizing Pancasila values, explored through cultural values in the community contextually. Therefore, the implementation of civic education in a community setting must incorporate Pancasila values derived from the community's philosophy of life and cultural heritage.